2017
DOI: 10.26496/bjz.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the African catfish, Clarias gariepinus (Burchell, 1822) in Kenya: implication for conservation and aquaculture

Abstract: ABSTRACT. African catfish, Clarias gariepinus, is an important species in aquaculture and fisheries in Kenya. Mitochondrial D-loop control region was used to determine genetic variation and population structure in samples of C. gariepinus from 10 sites including five natural populations (Lakes Victoria (LVG), Kanyaboli (LKG), Turkana (LTA), Baringo (LBA) and Jipe (LJP), and five farms (Sangoro Aquaculture Center (SAN), Sagana Aquaculture Centre (SAG), University of Eldoret Fish Farm (UoE), Kibos Fish Farm (KIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 12 publications
3
32
1
Order By: Relevance
“…This is supported by a negative D for all the populations, suggesting an increasing population size or a purifying selection at a locus (Tajima, ). The purifying selection that increases mutations at the locus could also be increasing genetic diversity at the locus, leading to the higher haplotype and nucleotide diversities in this study, compared with values reported by earlier studies in similar population (Barasa et al , ) and different populations (Roodt‐Wilding et al ., ; Barasa et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by a negative D for all the populations, suggesting an increasing population size or a purifying selection at a locus (Tajima, ). The purifying selection that increases mutations at the locus could also be increasing genetic diversity at the locus, leading to the higher haplotype and nucleotide diversities in this study, compared with values reported by earlier studies in similar population (Barasa et al , ) and different populations (Roodt‐Wilding et al ., ; Barasa et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…PCR conditions were as described by Nazia et al () and used by Barasa et al . (, ). Annealing temperature was 56° C. The success of the PCR reaction was confirmed by 2·0% agarose gel electrophoresis of PCR products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same time, the uncontrolled stocking and capture fishing have impacts on natural populations (e.g. fluctuating population size, decreasing genetic diversity, adaptability to changing environment and resistance to disease) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These markers are also widely used to estimate the population genetic values (such as variability, heterozygosity, inbreeding or genetic structure) [3,4]. Due to the economic importance of the African catfish, more and more genetic studies analyze the genetic variability, yield deterioration and the conservation genetic background of farmed [5,19] and natural [2] productions. However, the availability of the species-specific microsatellite markers suitable for detailed analysis of genetic resources are limited in number.…”
Section: Introductionmentioning
confidence: 99%